2022
DOI: 10.1101/2022.04.21.489003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple routes of adaptation to high levels of CIN and aneuploidy in budding yeast

Abstract: Both an increased frequency of chromosome missegregation (chromosomal instability) and the presence of an abnormal complement of chromosomes (aneuploidy) are hallmarks of cancer. Paradoxically, both chromosomal instability and aneuploidy are also associated with substantial decreases in cellular fitness. To better understand how cells are able to adapt to high levels of chromosomal instability, we previously examined yeast cells that were deleted of the gene BIR1, a member of the chromosomal passenger complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…During preparation of our manuscript Clarke et al reported strikingly similar conclusions from a completely orthogonal genetic screen for elevated rates of aneuploidy (Clarke et al, 2022). Notably, they developed a screen for suppressors of deficiency in BIR1, encoding a component of the chromosomal passenger complex, deletion of which leads to increased chromosome segregation defects and elevated aneuploidy.…”
Section: Discussionsupporting
confidence: 56%
“…During preparation of our manuscript Clarke et al reported strikingly similar conclusions from a completely orthogonal genetic screen for elevated rates of aneuploidy (Clarke et al, 2022). Notably, they developed a screen for suppressors of deficiency in BIR1, encoding a component of the chromosomal passenger complex, deletion of which leads to increased chromosome segregation defects and elevated aneuploidy.…”
Section: Discussionsupporting
confidence: 56%
“…In support of the second hypothesis, we found a mutation in the MPS1 gene specifically in a cell line with a karyotype that was highly divergent from the other adapted populations. Altered aneuploid karyotypes resulting from specific mutations has also recently been reported in yeast (Clarke et al 2022). In conclusion, the ability to recapitulate both general and cell line-specific aneuploidy patterns in human cells is an important step in determining the bases behind these patterns.…”
Section: Discussionmentioning
confidence: 80%